Narasi Gender dan Kekuasaan dalam Fenomena Poligami di Media Sosial: Kajian Sosio-Digital di Indonesia - Ahmad Mario Maulana; Ahmad Gyas Pawaj; Muhamad Farid Alfurqon; Agung Wiguna; Dea Lestari; M Dani Herlambang; M Al Fikri Najiullah; Aziz Faturokhman (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The circulation of polygamy narratives on Indonesian social media reflects an ongoing negotiation of gender relations and symbolic power in the digital public sphere. Situated within a socio-digital and critical gender perspective, this research examines how polygamy is constructed, legitimized, and contested across TikTok, Instagram, and YouTube through qualitative content and semiotic analysis of posts, comments, and user interactions. The findings reveal a dual pattern of discourse. On one side, dominant narratives normalize polygamy by framing male authority as moral, religiously grounded, and economically responsible, thereby reinforcing hierarchical gender relations and the symbolic legitimacy of masculine leadership within the household. On the other side, counter-narratives emerge through personal testimonies, critical reflections, and interactive debates that question claims of justice, highlight emotional and structural inequalities, and promote gender equity. The interactional features of digital platforms—such as comment threads, video responses, and algorithmic amplification—intensify both normalization and resistance, turning social media into a contested arena of meaning production. These dynamics demonstrate that digital discourse not only reflects existing cultural and religious values but actively reshapes public perception of polygamy. The analysis contributes to socio-digital studies by showing how gendered power relations are reproduced and challenged simultaneously within Indonesia’s contemporary media ecology.